Oil Price Fluctuations and the Future of Saudi Arabian Non-Oil Traded Sector: An Empirical Investigation - Algaeed, Abdulaziz Hamad (Journal of Economics and Behavioral Studies, 2017)
The major focus of this paper is to investigate theoretically and empirically the effects of non-linear oil price changes on Saudi manufacturing (traded) sector covering the period of 1970 till 2015, utilizing structural vector autoregressive (SVAR) approach. The Dutch disease syndrome will be clarified, and the impacts of oil price variations (increase and decrease) are investigated. Johansen’s testing procedure result asserts the existence of stable long-run relationship between real traded sector (MANUFACTURING), oil price increase and decrease, real government expenditure (GOEX), real exchange rate (REX), and the mining sector (MINING). The findings confirm that OILshock(+), and REX influence MANU negatively, while the spending effect, GOEX affects MANU positively. However, this could be attributed to the government efforts to nullify the Dutch disease symptoms. Given, the obtained tests’ results, the exchange rate REX appreciation confirms the existence of the Dutch disease, and consistent with the Dutch disease literature and findings. The Manufacturing sector harmed enough to the degree that government has to subsidize.